Negotiations Future of Inclusive Islamic Law: A Study of Abdullah Ahmed An-Naim's Sharia Deconstruction Thought - Syihabuddin , Muhammad; Hady , M. Samsul (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
Discourse on Islamic law is very important to be studied in more depth. This is because the study never ceases to be debated. In addition, Islamic law is required to continue to evolve and adjust to the times. The purpose of this paper is to understand 3 things: First, at a glance, an-Naim's thoughts related to Islamic law (sharia). Second, the methodology used in reformulating Sharia. The third is the idea of the future of inclusive Islamic law that spans the space and dynamics of the social development of society. The data were collected using a literature research model, a text-text approach in the form of books and articles. Then it was analyzed using data examination, classification, analysis, and followed by verification. The results found in the form of: 1) Sharia in an-Naim's view is not only fixated on the text of the Qur'an and Sunnah, but more than that it needs to be reinterpreted by looking at the context and reality that occurs today. 2) The methodology used by an-Naim is naskh-mansukh, by removing verses but not permanently (delaying the application of irrelevant verses). 3) The idea of an inclusive future for Islamic law is to provide space for every human being, the concept of equality in the realm of religion, ethnicity, race, and so on. This includes the renewal of criminal law, human rights, and international relations. The result that can be concluded is that Islamic law is acceptable to every community to be a role model that reflects progress and harmony with human life that has an impact on the benefit both in the Islamic world and internationally.